Protons on the line - Stancari, Giulio (Nature physics, 2024)
Stable regions in four-dimensional phase space have been observed by following the motion of accelerated proton beams subject to nonlinear forces. This provides insights into the physics of dynamical systems and may lead to improved accelerator designs.